An Agent Based Intelligent Distributed Control Paradigm for Manufacturing Systems. Issue 12 (2016) - Zhang, Haitao; Tang, Dunbing; Huang, Tengxiao; Xu, Chao
Abstract: In an increasingly dynamic and competitive environment with growing complexity, efficient processes are existentially for manufacturing companies. This implies the drive towards ever more high performance manufacturing systems, which are also robust against disturbances. This paper introduces a paradigm of distributed intelligent manufacturing control system based on agent, in which so-called smart components are embedded knowledge about the manufacturing process and its real time state. The application of the RFID (radio frequency identification) technology aids to realize smart components, to carry out the "physical communication" with the other equipments on the shop floor. The proposed paradigm can make the real-time decision based on the operating status of the system. It can be applied to the heterogeneous software and hardware of the existing system to carry out real-time dynamic reconfiguration. Result of the application on a test bed is used to show the effectiveness of the proposed approach.